Dissecting a biodiversity hotspot: The importance of environmentally marginal habitats in the Atlantic Forest Domain of South America. Issue 8 (8th June 2017) - Neves, Danilo M.; Dexter, Kyle G.; Pennington, R. Toby; Valente, Arthur S. M.; Bueno, Marcelo L.; Eisenlohr, Pedro V.; Fontes, Marco A.L.; Miranda, Pedro L. S.; Moreira, Suzana N.; Rezende, Vanessa L.; Saiter, Felipe Z.; Oliveira‐Filho, Ary T.
Abstract: Aim: We aimed to assess the contribution of marginal habitats to the tree species richness of the Mata Atlântica (Atlantic Forest) biodiversity hotspot. In addition, we aimed to determine which environmental factors drive the occurrence and distribution of these marginal habitats. Location: The whole extension of the South American Atlantic Forest Domain plus forest intrusions into the neighbouring Cerrado and Pampa Domains, which comprises rain forests ("core" habitat) and five marginal habitats, namely high elevation forests, rock outcrop dwarf‐forests, riverine forests, semideciduous forests and restinga (coastal white‐sand woodlands). Methods: We compiled a dataset containing 366, 875 occurrence records of 4, 431 tree species from 1, 753 site‐checklists, which were a priori classified into 10 main vegetation types. We then performed ordination analyses of the species‐by‐site matrix to assess the floristic consistency of this classification. In order to assess the relative contribution of environmental predictors to the community turnover, we produced models using 26 climate and substrate‐related variables as environmental predictors. Results: Ordination diagrams supported the floristic segregation of vegetation types, with those considered as marginal habitats placed at the extremes of ordination axes. These marginal habitats are associated with the harshest extremes of five limiting factors: temperature seasonality (high elevation and subtropical riverine forests), flammability (rock outcrop dwarf‐forests), high salinity ( restinga ), water deficit severity (semideciduous forests) and waterlogged soils (tropical riverine forests). Importantly, 45% of all species endemic to the Atlantic Domain only occur in marginal habitats. Main conclusions: Our results showed the key role of the poorly protected marginal habitats in contributing to the high species richness of the Atlantic Domain. Various types of environmental harshness operate as environmental filters determining the distribution of the Atlantic Domain habitats. Our findings also stressed the importance of fire, a previously neglected environmental factor.